2022
DOI: 10.30821/eunoia.v2i2.2098
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Media Sosial sebagai Media Pembelajaran Bahasa Indonesia

Abstract: Penelitian ini membahas penggunaan media sosial pada pembelajaran bahasa Indonesia. Media sosial yang dibahas pada penelitian ini yaitu facebook, Instagram, dan whatsapp. Peneliti menggunakan metode penelitian kualitatif. Hasil penelitian ini menunjukkan bahwa media sosial dapat dimanfaatkan sebagai media pembelajaran bahasa Indonesia. Penelitian ini juga memaparkan tahapan dan fungsi penggunaan beberapa fitur yang ada di aplikasi media sosial whatsapp, Instagram, dan facebook. Kelemahan media sosial yaitu ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 4 publications
0
6
0
11
Order By: Relevance
“…Exercise habits, on the other hand, show a positive but not significant association with mental health, indicating the need for further exploration and consideration of potential moderating factors [34]. The study also highlights the strong positive relationship between social support and mental health, emphasizing the importance of interpersonal relationships in shaping student well-being [35]. These findings have implications for interventions and policies aimed at improving mental health in the university environment in Indonesia [36].…”
Section: Discussionmentioning
confidence: 97%
“…Exercise habits, on the other hand, show a positive but not significant association with mental health, indicating the need for further exploration and consideration of potential moderating factors [34]. The study also highlights the strong positive relationship between social support and mental health, emphasizing the importance of interpersonal relationships in shaping student well-being [35]. These findings have implications for interventions and policies aimed at improving mental health in the university environment in Indonesia [36].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, advertisements are also beneficial as a medium for learning, including the learning of the Indonesian language. The utilization of advertisements as a learning medium has been extensively discussed in previous research, such as the study conducted by [10], titled "The Utilization of Advertisements as a Learning Medium for the Indonesian Language." The research discussed the use of advertisements as a medium for teaching the Indonesian language to elementary school students.…”
Section: B the Benefits Of Using Advertisements As A Learning Medium ...mentioning
confidence: 99%
“…It can also be concluded that using TikTok application can attract students speaking ability in language learning. Based on (Dewanta 2020), TikTok isn't as it were a media of excitement but moreover as a media of instruction, particularly those related to english dialect. There are numerous substance makers who give English learning substance, such as talking, elocution, lexicon, language structure and common botches since talking is one the four abilities in English which may be a prepare of communication by utilizing verbal shape, it isn't as it were for perusing or composing, but moreover for communicating the thoughts and conclusions (Perdana and Rianti 2021).…”
Section: Fostering Students' Fluency In Speakingmentioning
confidence: 99%